Komodifikasi Agama: Sebuah Strategi Pemasaran - Maya Kholida; Ita Rodiah (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2022)
Globalization has a very wide influence, including the shifts that occur in the industrial sector in the era of globalization. There are at least two shifting phenomena in the industrial sector today, namely the phenomenon of shifting from production to consumption issues, and shifting focus of capitalism from exploiting workers to exploiting consumers. Indonesia as a Muslim-majority country makes the Muslim market a very promising field for consumer exploitation for capitalists. The capitalists take advantage of the Islamic religion as a commodity to achieve maximum profit in exploiting Muslim consumers. In the beginning, religion was not something that was a commodity by the capitalists, it was made like a commodity that would bring in a lot of profit. This paper examines the phenomena that occur in society regarding the commodification of the Islamic religion. The purpose of this study is to examine the phenomenon of the commodification of Islam in Indonesia as a marketing strategy targeting the Muslim market. The method used in this research is a literature review or literature review, namely by reviewing and critically examining the findings, ideas, or knowledge in the literature. The result of this research is that in Indonesia the commodification of the Islamic religion absolutely occurs, and is a marketing strategy that is mostly carried out by business actors.